Performance evaluation of tool geometry of multi layer tungsten carbide tool when turning AISI 1045 Steel - Noordin Mohd. Yusof; Venkatesh, V. C. (Vellore Chelvaraj); Lok, Chen Wei; S. Sharif; A. Abdullah; All India Manufacturing Technology, Design and Research Conference (19th : 2000 : Chennai, India) (Skudai : Universiti Teknologi Malaysia, 2001)
20